Genetic Damage in Human Spermatozoa - Baldi, Elisabetta; Muratori, Monica; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
There are several types of damage that can be found in the male gamete. Genetic damage in spermatozoa can originate during spermatogenesis, or it can originate during transit in both male and female genital tracts. Damage can also be due to ageing, environmental or iatrogenic conditions, as well as to the protocols to cryopreserve and to select spermatozoa in assisted reproduction techniques. This book provides a comprehensive resource for all possible DNA damages in sperm, the relation to fertility and infertility, and possible transgenerational heritable effects.
Structure of chromatin in spermatozoa -- Genomic changes in spermatozoa of aging male -- Chromosomal aberrations and aneuploidies -- The sperm epigenome: implications for the embryo -- Paternal reprogramming of genome: transgenerational effects -- Alterations in protamination -- Sperm DNA fragmentation and base oxidation -- Iatrogenic Genetic damage -- Sperm selection: effect on sperm DNA quality -- Effect of antioxidant treatments on sperm genetic damage -- Index.
Keywords: Medicine; Human genetics; Endocrinology; Reproductive Medicine; Biomedicine; Human Genetics; Endocrinology; Reproductive Medicine